The Effect of Service Quality and Toll Price Rates on Toll Road User Satisfaction (Case Study on Kelapa Gading – Pulo Gebang Toll Road) - Khairunnisa Pertiwi Rahaviana; Nunung Widyaningsih (CV. Syntax Corporation Indonesia, 2024)
Toll road construction is one of the main supporting aspects in the process of accelerating Indonesia's national development. However, along with population growth and regional development, road infrastructure is increasingly filled with various modes of transportation which ultimately causes buildup and congestion. The construction of toll roads in Jakarta is one alternative to break down congestion in the city. The construction of the Kelapa Gading - Pulo Gebang Toll Road is expected to be able to increase road capacity so as to facilitate transportation between the two regions. However, the varied toll rates cause different perceptions in its users. Toll tariff determination is generally oriented towards financial analysis which results in not being commensurate with the ability (Ability To Pay) and desire (Willingness To Pay) as well as the determination of the ideal tariff of the community as toll road service users. This research uses a descriptive method with a quantitative approach. Data collection using questionnaires and documentation. The research population of the entire Jakarta city community in 2022 is 10,679,951 people, the number of samples calculated using the Slovin method resulted in 100 respondents selected through certain criteria. Data analysis uses validity tests, reliability tests and descriptive analysis. The results showed that the level of driver satisfaction with the quality of service of the Kelapa Gading - Pulo Gebang Toll Road was in the